Evaluación de biofertilizantes líquidos en el desarrollo vegetativo del cultivo de café (Cofeea arábica). - Albarracín Palma, Leonilde Adriana (2020)
The project was carried out at the “Sacha Wiwa” Experimental Center belonging to the SEIC Foundation in La Maná. The objectives of the research were: to evaluate the growth indicators in coffee plants at the Sacha Wiwa Experimental Center. Determine the most effective type of bio fertilizer in crop growth. Analyze the coffee variety that best agronomic development present with the bio fertilizer concentrations. The randomized block design was used with a 4x4 factorial arrangement with the application of 4 concentrations of bio fertilizer, in 4 coffee varieties. The variables evaluated were: plant height, trunk diameter, leaf perimeter at 30, 60, 90 and 120 days. The results obtained were: higher plant height with the Ecorobusta variety in bio fertilizer applications with 20% concentration of organic matter obtaining 31.68 centimeters at 30 days, at 60 days it obtained 42.22 centimeters, while at 90 and 120 days it reached get 53.44 and 61.61 centimeters respectively. The variable trunk diameter results were: NP-3056 at 30, 60 and 90 days with 1.23, 1.35 and 1.83 centimeters, at 120 days the highest result was evidenced with the Ecorobusta variety at 20% organic matter with 1.49 centimeters. The foliar perimeter that obtained the greatest result was the Ecorobusta variety with 20% concentrated biofertilizer of M.O. At 30 days it obtained 80.00 centimeters, at 60 and 90 days it reached a foliar perimeter of 86.32 and 93.56 centimeters. At 120 days the highest rate of leaf perimeter was achieved with the Ecorobusta with 106.61 centimeters.